Design, development and validation of a photogrammetric system for kinematic assessment of competition in team sports - J. Granda; V. M. Soto; J. C. Barbero (Asociación Española de Ciencias del Deporte, 2010)
The valuation and quantification of the displacements of the player throughout the execution of its movements during its intervention in the parties, allow to obtain very excellent data to be able to deduce the physical loads which this one is put under (Hughes and Franks, 1997). This knowledge of the physical exigencies supported by the player during the competitive activity provides very useful and excellent information for trainers and physical trainer on the demands of the sport and the tipology of the efforts. The intention of the present work is to present the main characteristics a developed fotogrametric system for the kinematic analysis of the competition in equipment sports. The developed method allows realize a kinematic analysis by means of bidimensional photogrammetry quantifying of precise and trustworthy form the registered displacements. It generates information referring to as much kinematic parameters (distances, speeds, accelerations) like of use of the space (frequented areas), very useful variables to deduce the physical loads which one is put under the sportsman during the competition, providing a more specific knowledge of each one of the studied sport specialties. KEY WORDS: Kinematic analysis, team-sports, competition.